Peak alpha frequency is related to the degree of widespread pain, but not pain intensity or duration, among people with urologic chronic pelvic pain syndrome - Rocco Cavaleri; Natalie J. McLain; Matthew Heindel; Andrew Schrepf; Larissa V. Rodriguez; Jason J. Kutch (PAIN Reports)
Abstract. Introduction:. Effective prevention and management strategies for chronic pain remain elusive. This has prompted investigations into biomarkers to better understand the mechanisms underlying pain development and persistence. One promising marker is low peak alpha frequency (PAF), an electroencephalography (EEG) measure that has been associated with increased sensitivity during acute experimental pain. However, findings regarding the relationship between PAF and chronic pain are variable, potentially due to disparate levels of central sensitization among chronic pain populations. This is evidenced by the variable extent of widespread pain, a phenotypic marker for central sensitization, observed across individuals with chronic pain. Objective:. To explore the impact of widespread pain on PAF among people with chronic pain. Method:. Thirty-eight individuals with urologic chronic pelvic pain syndrome were categorized as having widespread (n = 24) or localized (n = 14) pain based upon self-reported body maps. Electroencephalography data were collected under resting conditions, and PAF was determined using spectral analysis. Results:. Participants with widespread pain had a significantly lower global average PAF than those with localized pain, after controlling for age and sex. This relationship persisted even when accounting for pain intensity and duration. Peak alpha frequency differences were observed across all EEG electrodes, particularly in the sensorimotor and occipital regions. Conclusion:. Preliminary findings suggest that PAF may represent a potential biomarker for central sensitization in chronic pain, highlighting the importance of considering pain distribution in chronic pain research. Future studies with larger samples should investigate the neural mechanisms underlying these observations and the clinical utility of PAF in diverse chronic pain populations.